Revealing the impact of strain in the optical properties of bubbles in monolayer MoSe2. Issue 15 (29th March 2022) - Covre, F. S.; Faria, P. E.; Gordo, V. O.; de Brito, C. Serati; Zhumagulov, Y. V.; Teodoro, M. D.; Couto, O. D. D.; Misoguti, L.; Pratavieira, S.; Andrade, M. B.; Christianen, P. C. M.; Fabian, J.; et al.
Abstract : We have investigated the optical properties of strained MoSe2  monolayer bubbles at low temperature. We have observed a red-shift of the exciton and trion emissions, a reduction of the trion binding energy and an enhancement of the valley  g -factors. Abstract : Strain plays an important role for the optical properties of monolayer transition metal dichalcogenides (TMDCs). Here, we investigate strain effects in a monolayer MoSe2 sample with a large bubble region using μ-Raman, second harmonic generation (SHG), μ-photoluminescence and magneto μ-photoluminescence at low temperature. Remarkably, our results reveal the presence of a non-uniform strain field and the observation of emission peaks at lower energies which are the signatures of exciton and trion quasiparticles red-shifted by strain effects in the bubble region, in agreement with our theoretical predictions. Furthermore, we have observed that the emission in the strained region decreases the trion binding energy and enhances the valley g -factors as compared to non-strained regions. Considering uniform biaxial strain effects within the unit cell of the TMDC monolayer (ML), our first principles calculations predict the observed enhancement of the exciton valley Zeeman effect. In addition, our results suggest that the exciton–trion fine structure plays an important role for the optical properties of strained TMDC ML. In summary, our study provides fundamental insights on the behaviour of excitons and trions in strained monolayer MoSe2 which are particularly relevant to properly characterize and understand the fine structure of excitonic complexes in strained TMDC systems/devices.